LncRNA-ANAPC2 and lncRNA-NEFM positively regulates the inflammatory response via the miR-451/npr2/ hdac8 axis in grass carp. Issue 128 (September 2022) - Pang, Yifan; Li, Liuyang; Yang, Yuyue; Shen, Yubang; Xu, Xiaoyan; Li, Jiale
Abstract: In grass carp ( Ctenopharyngodon idella ), septicemia is a systemic inflammatory response to bacterial infection and could be leaded to lethality. MiR-451 involved in septicemia progression has been reported. However, the underlying mechanism of miR-451 in septicemia induced inflammatory response remains to be revealed. In the present study, miR-451 was highly expressed in Aeromonas hydrophila induced CIK cells, opposite to lncRNA-ANAPC2 and lncRNA-NEFM expression. Furthermore, we found that miR-451 interacted with lncRNA-ANAPC2 and lncRNA-NEFM, also targeted the 3′ UTR of npr2 and hdac8 . In CIK cells, the inhibition of npr2 and hdac8 were down-regulated by lncRNA-ANAPC2 and lncRNA-NEFM knockdown, while downstream proinflammatory factors were inhibited. In a word, this study indicates that lncRNA-ANAPC2 and lncRNA-NEFM regulation the LPS-induced progression of inflammatory response by modulating miR-451/ npr2 / hdac8 axis. Highlights: Previous studies on miR-451 and related target genes have focused on the mammalian level. This study is the first time to study its immune function in grass carp. This paper puts forward the hypothesis that lncRNA may competitively bind miRNA to alleviate its degradation of target genes and inhibit the translation of target genes. LncRNA-ANAPC2 and lncRNA-NEFM can interact with miR-451 to activate NF-κB signaling pathway promotes the release of pro-inflammatory cytokine. It plays an important role in the innate immunity of grass carp.